Fatal Intoxications in a Forensic Autopsy Material from Epirus, Greece, During the Period 1998‐2010. Issue 2 (26th October 2012) - Boumba, Vassiliki A.; Georgiadis, Minas; Mirescu, Nikolae; Vougiouklakis, Theodore
Abstract: In this retrospective study, we report the epidemiological characteristics of all poisoning deaths in Epirus, Greece, from 1998 to 2010; we present the toxicological findings and the statistical evaluation of the results. This is the first detailed scientific report on all the officially certified poisoning deaths concerning part of the Greek population. A total of 126 poisoning fatalities were recorded, 67 of them being mono‐intoxications (53.2%). The cause of poisoning was as follows: drugs of abuse (60%); carbon monoxide (19.8%); pesticides (9.5%); corrosives (4.8%); pharmaceuticals (4.8%); and spider bite (0.8%). The most frequently detected poisonous substances were as follows: heroin (65 cases), ethanol (55), benzodiazepines (42), carbon monoxide (25), cocaine (17), cannabinoids (17) and pesticides (12). Increasing tendency in poisoning death rates was recorded, due to an increase in accidental poisoning deaths attributed mainly to drugs of abuse (total, accidental, and drugs‐of‐abuse poisoning death rates per 100, 000 inhabitants per year were 1.87, 1.19, and 0.79, respectively, in the period 1998–2002 and 3.97, 3.41, and 2.55, respectively, in the period 2007–2010).